Reduction Surgery of Giant Hemifacial Neurofibromas: A Case Report - Ruby Riana A; Sitti Rizaliyana; Radias Dwi Padmani; Retno Handajani; S. Perdanakusuma (Indian Journal of Forensic Medicine & Toxicology, 2022)
Neurofibromatosis type 1 (NF-1), first described by Von Recklinghausen (1882), is an autosomal dominant disease caused by a spectrum of mutations in NF-1 gene. We reported a case of giant facial neurofibromas in 26 years old male patient without family history of neurofibromatosis type 1. Features typical of neurofibroma, including an enlarged nerve fascicle composed of elongated nuclei and scant cytoplasmic cells, were identified. Excision was performed with preservation of parotid duct. The mass weight was about 5,5 kg. There were some challenges during the procedure, such as bleeding, hypovolemia, and preservation of vital structure.